The global connections of Gandhāran art : proceedings of the Third International Workshop of the Gandhāra Connections Project, University of Oxford, 18th-19th March, 2019 - Rienjang, Wannaporn,; Stewart, Peter, 1971- (Archaeopress Archaeology, 2020)
This volume addresses directly the question of cross-cultural influence on and by Gandharan art. The contributors wrestle with old controversies, particularly the notion that Gandharan art is a legacy of Hellenistic Greek rule in Central Asia and the growing consensus around the important role of the Roman Empire in shaping it.